Energy efficiency and fluctuations in CO₂ emissions - Soojin Jo; Lilia Karnizova (Bank of Canada, 2021)
CO2 emissions are commonly perceived to rise and fall with aggregate output. Yet many factors, including energy-efficiency improvements, emissions coefficient variations and shifts to cleaner energy, can break the positive emissions-output relationship. To evaluate the importance of such factors, we uncover shocks that by construction reduce emissions without lowering output. These novel shocks explain a substantial fraction of emissions fluctuations. After extensively examining their impacts on macroeconomic and environmental indicators, we interpret these shocks as changes in the energy efficiency of consumer products. Our results imply that models omitting energy efficiency likely overestimate the trade-off between environmental protection and economic performance.
Keywords: E32; Q43; Q50; Q55; 330; Climate change; Econometric and statistical methods; Business fluctuations and cycles